KEMISKINAN PADA MASYARAKAT DESA SOFAN KECAMATAN TALIABU TIMUR SELATAN KABUPATEN PULAU TALIABU - Suti Sutrisno Lateba; Ferdinand Kerebungu; Abdul Rasyid Umaternate (Labor Program Studi Pendidikan Sosiologi, 2021)
The problem in this study is poverty in the people of Sofan Village, South East Taliabu District, Taliabu Island Regency. The purpose of this study was to assess poverty in the community of Sofan Village, South East Taliabu District, Taliabu Island Regency. This study uses qualitative methods with data collection techniques used are observation, documentation and interviews. The data analysis technique used in this study was the Milles and Huberman technique. Determination of informants in this study using purposive sampling technique. The results show that in general the Sofan Village community is a poor community, and the factor that causes poverty in the Sofan Village community is the low education factor, this lack of employment can be seen in general from the work of the community is farmers and fishermen. Another thing that causes poverty is the lack of income and the habit of some people who were still sitting before working. Another factor that causes poverty in the people of Sofan Village is the attitude of being dependent on other parties, especially the Government. This attitude of being too dependent on others is what causes them to live in poverty.